Dielectric characteristics of the high heat-conducting AlN-ceramics in the frequency range of 3–93 GHz - Chasnyk, V. I.; Fesenko, I. P. (Technology and design in electronic equipment, 2013)
The article presents the results of experimental measurements. It is shown that the behavior of the dielectric constant and dielectric loss tangent in the investigated frequency range is due to the lack of relaxation processes in ceramics associated with the orientation polarization and to weak influence of ion and electron polarization.